ANALISIS STABILITAS TIMBUNAN DENGAN PERKUATAN GEOTEKSTIL DAN CERUCUK - Fahrita Sari; Istiatun Istiatun (Politeknik Negeri Jakarta, 2022)
On the Serpong–Balaraja Toll Road Section 1A (STA 4+550–SSTA 4+900), there is a swamp area that is designed to have an embankment, so repair and reinforcement of the soil are needed. Therefore, this analysis aims to analyze the safety factor and consolidation settlement on the original soil. In addition, this analysis was carried out on soil replacement, geotextile, a combination of soil replacement and geotextile methods, and cerucuk using Plaxis 2D v20. The original soil conditions were also analyzed by the Fellenius method. The analysis results on the original soil conditions with Plaxis 2D v20 indicated a collapse, while with the Fellenius method the safety factor was 1.5, so it was not safe. Based on the methods used, only the geotextile method with variations of five layers of geotextile in post-construction is not safe. In soil replacement and soil replacement with geotextiles, the safety factor is relatively the same between 5.5 and 8 meters of replacement soil. Therefore, the thickness of the replacement soil has an optimum point where the addition of the thickness of the replacement soil is not linear with an increase in the safety factor. The consolidation settlement in the geotextile method is greater than in other methods. The detailed explanation will be developed on the writing paper below. Keywords: Cerucuk, Consolidation Settlement, Geotextile, Safety Factor, Soil Replacement.